Recurrence of hepatocellular carcinoma as a mixed hepatoblastoma after liver transplantation. Issue 4 (1st October 1999) - Dumortier, J; Bizollon, T; Chevallier, M; Ducerf, C; Baulieux, J; Scoazec, J Y; Trepo, C
Abstract : BACKGROUND: Hepatoblastoma is an exceptional cause of primary malignant liver tumour in the adult. PATIENT: The case is reported of an adult patient transplanted for alcoholic cirrhosis complicated by multifocal hepatocellular carcinoma in whom a recurrence in the form of a mixed hepatoblastoma invading the whole transplanted liver developed three months after liver transplantation. METHODS: Complete clinical, histopathological, and immunohistochemical data were reviewed. RESULTS: The recurrent tumour invaded the whole liver. The major component was a mixed hepatoblastoma, with an epithelial component expressing cytokeratin and a mesenchymal component expressing vimentin. The tumour also contained a minor hepatocarcinomatous component expressing α fetoprotein. The rapid growth of the tumour prevented any attempt at treatment. Although direct evidence is lacking, the most likely hypothesis to explain the observations is a marked phenotypic change in the initial malignant population at recurrence. CONCLUSION: This case supports a possible filiation between hepatocellular carcinoma and hepatoblastoma in adults.